A Crisis for Peace?: Climate Change, Environmental Peacebuilding, and Interfaith Harmony in Indonesia - Khaira, Annisa Nabilatul; Ranti, Munif Arif (As- Sakinah Law Firm & Society of Visual Informatics, 2024)
This research aims to analyze mutually reinforcing relations between climate change and interfaith harmony. Interfaith peace in the context of climate change can be created more effectively by building harmony and peace in Indonesia as a plural state because alleviation is no longer segmented to faith-based efforts alone. This research uses a qualitative method with a literature study approach. Based on the conceptual framework of environmental peacebuilding, this study found four important points: (1) climate change and interfaith harmony are mutually reinforcing; and (2) the shift from a faith-based approach to interfaith-based approach represents a more effective Environmental Peacebuilding effort (3) The existence of bottom-up initiatives executed in the frame of interfaith cooperation shows that the role of local communities is increasingly significant in environmental peacebuilding efforts in Indonesia. (4) Interfaith communities can conduct advocacy to build a more critical society by addressing national development that intersects with environmental interests.